Activity Test of Methanol Extract of Young Stem Bark of Semambu rattan Plant (Calamus Scipionum Lour) with DPPH Method - Hasana, Nazria; Yani, Dwi Fitri; Wijayanti, Fitria (Walisongo Journal of Chemistry, 2024)
The Semambu rattan (Calamus scipionum Lour) plant contains phenolic compounds, such as flavonoids and polyphenols that have the ability as antioxidants. Therefore, the community often consumes C scipionum Lour, and the stiff stems are made of crafts. However, the skin, the content of which is not scientifically known, is currently considered a waste in the community. This study was conducted to determine the results of phytochemical tests and the activity of methanol extract of young bark of the Semambu rattan plant (C. scipionum Lour). The bark of young Semambu rattan stems is extracted by maceration, and then the extract obtained is carried out by phytochemical screening. Antioxidant acrypability was measured using the DPPH method at a wavelength of 517nm. The results of phytochemical testing of young bark extract of C. scipionum Lour contain flavonoids, saponins, tannins, alkaloids and terpenoids. The research results on antioxidant young stem bark C. scipionum Lour with positive control in the form of ascorbic acid obtained results IC50 = 65.10 ppm, which is classified as a potent antioxidant. The conclusion of this study is that the extract of the young bark of Semambu rattan (C. scipionum Lour) can be used as an alternative antioxidant.